The effects of Pandanus tectorius leaf extract on the resistance of White-leg shrimp Penaeus vannamei towards pathogenic Vibrio parahaemolyticus - Anupa Anirudhan; Mat Taib Mimi Iryani; Yosie Andriani; Patrick Sorgeloos; Min Pau Tan; Li Lian Wong; Wen Jye Mok; Wang Ming; Liang Yantao; Cher Chien Lau; Yeong Yik Sung (Fish and Shellfish Immunology Reports, 2023)
Pandanus tectorius leaf extract effect on the White-leg shrimp Penaeus vannamei tolerance against Vibrio parahaemolyticus were investigated in this study. Thirty shrimp post-larvae measured at approximately 1 cm were exposed for 24 h to 0.5, 1, 2, 3, 4, 5 and 6 g/L leaf extract and subsequently observed for survival and immune-related genes expression (Hsp70, ProPO, peroxinectin, penaeidin, crustin and transglutaminase), followed by determination of their tolerance and histological tissue profiles upon Vibrio challenge. Survival of shrimps treated with 6 g/L of leaf extract improved by up to 95% to controls. Hsp70, crustin, and prophenoloxidase mRNA levels were observed to be 8.5, 10.4, and 1.5-fold higher, respectively. Histopathological analysis of the hepatopancreas and the muscle tissues revealed major tissue degeneration in Vibrio-challenged shrimps but not in shrimps primed with P. tectorius leaf extract. Of all the dose examined, the best pathogen resistance results were obtained with a 24 h incubation of shrimp in 6 g/L P. tectorius methanolic leaf extract. The tolerance towards V. parahaemolyticus might be associated with the increased regulation of Hsp70, prophenoloxidase and crustin upon exposure to the extract, all immune-related proteins essential for pathogen elimination in Penaeid shrimp. The present study primarily demonstrated that P. tectorius leaf extract is a viable alternative for enhancing P. vannamei post-larvae resistance against V. parahaemolyticus, a major bacterial pathogen in aquaculture.